A Case Study to Evaluate the Potential of Nasya Karma and Ayurvedic Formulations against Post Covid Chronic Bronchitis - Ninama, Raju; Verma, Archana; Nagle, Anil; Pati, R K; Meshram, Rajesh (International Research Journal of Ayurveda & Yoga, 2023)
Background- SARS-COV-2, β type corona virus affects nearly all world population after appearing in Wuhan in Nov. 2019. In Covid-19 related bronchitis there is an issue of excessive sputum production in the airways (Kaphastheevan), resulting in coughing (Kasa) and chest tightness.This recurrent cough and ongoing chest discomfort affect one’s quality of life. Aim & Objectives- Aim of this study is to create an Ayurvedic protocol (Shodhan Chikitsa -Nasya therapy and Shaman Chikitsa – Chitrak Haritaki, Sitopaladi Churna, Tankan Bhasma, Swarnavasant Malti Rasa) for treatment of post Covid 19 related chronic bronchitis. Material & Methods- It is a case of 27yrs old female presented with complain of breathlessness, cough especially at night with expectoration. Assessment was done on the basis of symptoms, radiological findings (Chest X-ray PA View) and PFT (FVC & FEV1). Result- There was relief in Subjective Parameters such as Cough (Kasa), Dyspnoea (Shwasakashtata), Chest tightness (Urashool), Wheezing (Ghurghurak), Sputum and Sleep (Nidra). This Ayurvedic treatment yielded more improvement in the value of FEV1.0 (L), FVC (L), FEV1.0/FVC (%) after treatment. Discussion- Shodhan (Anu Tail Nasya) and Shaman (Chitrak Haritaki, Sitopaladi Churna, Tankan Bhasma, Svarnvasant Malti Rasa) Chikitsa have mainly Vata Kaphahara action. This Case study of COVID-19 related Chronic Bronchitis is highly effective in subsiding the all symptoms of Post COVID Chronic Bronchitis and also improving the Pulmonary Function.